2004
DOI: 10.1016/j.ijdevneu.2004.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and cellular consequences of increasing serotonergic activity during brain development: a role in autism?

Abstract: The hypothesis explored in this review is that the high levels of serotonin in the blood seen in some autistic children (the so-called hyperserotonemia of autism) may lead to some of the behavioral and cellular changes also observed in the disorder. At early stages of development, when the blood-brain Barrier is not yet fully formed, the high levels of serotonin in the blood can enter the brain of a developing fetus and cause loss of serotonin terminals through a known negative feedback function of serotonin d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
192
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(201 citation statements)
references
References 114 publications
5
192
0
Order By: Relevance
“…Another recent rodent model lends support to our hypothesis of the role played by early serotonergic innervation in the etiology of autism. Although Whitaker-Azmitia and colleagues [66,123] propose a hyperserotonemic model of autism, their hypothesis is ultimately consistent with our own. In their studies, perinatal rat pups were exposed to a serotonergic agonist from mid-gestation to PND 20.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Another recent rodent model lends support to our hypothesis of the role played by early serotonergic innervation in the etiology of autism. Although Whitaker-Azmitia and colleagues [66,123] propose a hyperserotonemic model of autism, their hypothesis is ultimately consistent with our own. In their studies, perinatal rat pups were exposed to a serotonergic agonist from mid-gestation to PND 20.…”
Section: Discussionsupporting
confidence: 87%
“…Although somewhat variable, a number of recent reports indicate an association between variations in the gene that encodes SERT and a susceptibility to autism [33,43,112]. Whitaker-Azmitia and colleagues [66,123] propose a perinatal hyperserotonemic animal model for the pathophysiology of autism. They suggest that the excessively high 5-HT from the blood of the growing fetus crosses the forming blood brain barrier, gains access to the developing brain, and ultimately causes a loss of 5-HT terminals in cerebral cortex via a negative feedback system mediated by 5-HT receptors.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, increased 5-HTergic activity during development causes loss of 5-HT terminals in the adult. 169 Several drug treatment studies have shown this negative feedback of 5-HT on development of 5-HTergic neurons. [170][171][172][173][174][175][176][177][178][179][180] Alterations in 5-HTT function 181 and hypothalamic 5-HT levels 182 may be in part responsible for altered HPA axis activity in adult PS offspring.…”
Section: Stressmentioning
confidence: 99%
“…168 In addition to influencing the development of target regions, 5-HT also has a negative feedback effect on the developing fetal 5-HT neurons. 169 As 5-HT neurons develop, 5-HT levels increase until a point is reached at which the growth is curtailed through a negative feedback mechanism. 169 When 5-HT levels are high early in development, when the blood-brain barrier is not fully formed yet, 5-HT can enter the brain of a developing fetus and thus cause loss of serotonin terminals through negative feedback.…”
Section: Stressmentioning
confidence: 99%
See 1 more Smart Citation